Management of Sambar Deer (Cervus Unicolor Brookei) Under Agroforestry System in Sarawak - Jiwan, Dawend (2001)
Sambar deer breeding under existing forest plantation with local Sabal Tapang community participation was one of the Agroforestry projects implemented in Sarawak aimed at bringing socio-economic benefits to the shifting cultivators and to strike a balance in nature conservation. The research and observation conducted during the implementation of this agroforestry deer breeding focused on the animal performance, initial effect of deer browsing behaviour on the plantation and attitude and perception of adjacent communities towards the overall agroforestry systems in Sabal. Brody's Growth Model was the most suitable model for deer production under this system. The appropriate age of venison production was about two years when the animal weighed around 74.2 kg. Sambar deer was found to have no definite breeding season. The sex ratio of fawn male to female was 1:1.5, female became sexually mature at 23.1 months, fawning interval was 11.3 months and gestation was 257 days. The period of stag which did not cause damage to vegetation was 4.7 months compared to the long period of 6.9 months of destructiveness to the trees stand as a result of rubbing and territorial marking. There were 22 known families of woody plant and another 10 families of non-woody plant found in the 12-year old Acacia mangium plantation. A total of more than 21 species were eaten by 14 heads of Sam bar deer over a total observation of 65 days within an area of 8.0 ha. Sambar deer browsing was highest in Ficus spp. (34%) for all leaves, fruits and bark; followed by Dillenia sp. shoots (30%); Agrostistachys sp. leaves (8%) and Macaranga spp. leaves (7%). The maximum limit of browsing was observed at height of 4 m with diameter of less than 3.8 cm. The browsing pattern based on nutritional selectivity was shown in species with high dry matter digestibility, crude protein, fibre, potassium, calcium, copper and zinc content. The other factors affecting the browsing pattern were microhabitat and closeness to perimeter fence. It was found that more than 70 percent of tracks and trampling happened near to stream and near to fence compared to only 20 percent observed in the middle of paddock. The criteria for villages acceptance of agroforestry projects were (1) ease of management; (2) fast economic returns; (3) proximity to village and; (4) involving direct participation oflocal people in most of the activities.